(untitled) (Journal of Dhaka Medical College, 2010)
A prospective study of 100 cases of preterm pregnancy was done in the Department of Obstetrics & Gynaecology of Dhaka Medical College Hospital and Mitford Hospital, Dhaka from September 2002 to August 2003. The incidence and indications for caesarean section operation were eclampsia 24%, preeclampsia 20%, antepartum haemorrhage (APH) 15%, premature rupture of membrane (PROM) 8%, PROM with chorioamnionitis 4%, preterm labour with previous caesarean section 9%, foetal distress with labour pain 7%, less foetal movement 6%, malpresentation with cord prolapse 3%, multiple pregnancy 2% and diabetes mellitus with polyhydramnios 2%. Emergency caesarean section was done in 98 cases and elective operation in 2 cases. Live birth was 93% and perinatal mortality was 32%. Neonatal morbiditites were prematurity and birth asphyxia. Maternal mortality in preterm caesarean section was 16%. Key words: Preterm pregnancy; Caesarean section; Indication; Outcome. DOI: 10.3329/jdmc.v18i2.6271 J Dhaka Med Coll. 2009; 18(2) : 124-126